Earthrise : Apollo 8 and the photo that changed the world - Gladstone, James, 1969- (Owlkids Books, 2018)
"Earthrise tells the story of the first time the planet Earth was photographed in colour from space. The photo, later called Earthrise, was taken in 1968 by the astronauts on Apollo 8, the first US space mission to break free of Earth's orbit and circle the Moon. The Apollo 8 astronauts were surveying the lunar surface for places to land future missions. As they were charting the Moon, they happened to look up just as Earth, in a flash of color and life, was rising above the darkness of space and the dead rock of the Moon. The sight had a profound effect on the astronauts-and the photo they took had a similarly profound effect when it was published back on Earth in newspapers and magazines. By making clear that Earth was, and is, at heart, a world without borders, a home to all peoples, the photo's mind-bending shift in perspective is credited for galvanizing the fledgling environmental movement and sparking hope in a year of global unrest. And, to quote from the last page of the book, 'in a time when people still struggle to live together in peace, that picture of the rising Earth is as powerful now as it was in 1968'."--